Catalytic Decomposition of Azo Dye Using ZnO in Sunlight - Ram Babu Pachwarya; Euis Nurul Hidayah; Dr. Rekha Kashyap; A.L. Ramanathan; R.C. Meena; Pramod Kumar Meena; Syadzadhiya Q.Z. Nisa (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2022)
The degradation of azo is a challenge for environmentalists. Catalytic decomposition of azo dyes by ZnO heterogeneous photocatalysis and the influence of operating parameters such as light intensity, temperature, amount of ZnO catalyst, solution pH and amount of pollutants. It has been observed that ZnO catalysts is quite capable of removing azo dyes in the presence of sunlight. We can use the same catalyst over and over, and it works well every time. We recovered 99% clear water within a few hours of exposure to sunlight.